Electroejaculation Increases Low Molecular Weight Proteins in Seminal Plasma Modifying Sperm Quality in Corriedale Rams - Ledesma, Alba; Manes, Jorgelina; Cesari, Andreina; Alberio, Ricardo; Hozbor, Federico Andres (Wiley, 2019)
This study was conducted to evaluate the effect of seminal collection method (artificial vagina or electroejaculation) on the protein composition of seminal plasma and sperm quality parameters in Corriedale rams. To address this question, we assessed the effect of seminal collection method on motility, plasma membrane integrity and functionality, mitochondrial functionality and the decondensation state of nuclear chromatin in sperm cells. Volume, pH, osmolarity, protein concentration, total protein content and protein profile using sodium dodecyl sulphate–polyacrylamide gel electrophoresis (SDS‐PAGE) and 2‐D polyacrylamide electrophoresis of seminal plasma collected with artificial vagina and electroejaculation were also analysed. The main findings from this study were that ejaculates obtained with electroejaculation had (i) a higher number of spermatozoa with intact plasma membrane and functional mitochondria and (ii) a higher proportion of seminal plasma, total protein content and relative abundance of low molecular weight proteins than ejaculates obtained with artificial vagina. Five of these proteins were identified by mass spectrometry: binder of sperm 5 precursor; RSVP14; RSVP22; epididymal secretory protein E1 and clusterin. One protein spot with molecular weight of approximately 31 kDa and isoelectric point of 4.8 was only found in the seminal plasma from electroejaculation.